The H2-A Class II molecule α/β-chain cis-mismatch severely affects cell surface expression, selection of conventional CD4+ T cells and protection against TB infection - Logunova, Nadezhda; Kapina, Marina; Kondratieva, Elena; Apt, Alexander (Frontiers in Immunology, 2023)
To dissect the role of the part of the H2 complex comprised of the MHC-II genes in the control of tuberculosis (TB) infection, we previously established a panel of recombinant congenic mouse strains bearing different segments of the H2j haplotype on the B6 (H2b) genetic background. Fine genetic mapping, gene sequencing and assessment of TB phenotypes resulted in identification of the H2-Ab gene as a major factor of TB control. In this work, we further narrowed the MHC-II H2j interval by spotting a new recombination event and establishing a mouse strain B6.I-103 in which j/b recombination occurred within the coding sequence of the H2-Ab gene. Unexpectedly, a novel H2-Aαb/AβjE0 haplotype provided exclusively high susceptibility to TB challenge. Immunologic analysis revealed an altered CD4+ T-cell selection and maintenance in B6.I-103 mice, as well as seriously impaired expression of the H2-Aαb/Aβj molecule on the surface of antigen presenting cells. Unlike previously reported cases of Class II malfunctioning, the defective phenotype arose not from strong structural mutations, but from regular recombination events within the MHC-II recombination hot spot region. Our findings provide evidence that Class II α/β-chain cis-allelic mismatches created by regular genetic recombination may severely affect immune system functioning. This issue is discussed in the context of the MHC evolution.